Circular economy of food packaging: cost and functional preferences of Thai consumers and restaurants in off-premises food services - Manatsikarn Cruecha-Em; Md. Julhaz Hossain; Anchalee Nuansri; Farhad Zulfiqar (Sustainable Futures)
The increasing waste from food delivery services necessitates a comprehensive understanding of the cost and functional preferences of key stakeholders concerning food packaging solutions. Therefore, this study investigated the cost and functional preferences of restaurants and consumers toward packaging solutions for off-premises food services through a survey of 100 restaurants and 100 consumers in Greater Bangkok. Key informant interviews were conducted to understand the cost of the reuse model and food packaging attributes. Discrete choice experiments using Conjointly, conditional logit, and multinomial logit models were used for analysis. This study focused on packaging solutions including non-recyclable plastic containers, and four circular packaging solutions namely recyclable plastic containers, bioplastic containers, natural fiber containers, and durable containers with a reuse model. Considering costs, environmental consequences, and attribute preferences of both restaurants and consumers, the findings revealed that 1) restaurants valued price and materials, preferring recyclable or biodegradable solutions, however, they were not willing to pay for a reuse model, 2) consumers valued recyclable or biodegradable and reuse model materials the most with high preferences and willingness to pay for both, 3) recyclable plastic containers and natural fiber containers received the highest total utility per unit of cost. Therefore, it is recommended that the circular transition be supported by the promotion of natural fiber containers, and cost transfer to consumers and third-party service providers to support reuse model adoption. This study articulates theoretical and policy implications and provides directions for policymakers, academics, food delivery service firms, food packaging enterprises, and other relevant stakeholders.